CURRENT TREND IN LAMIACEAE AS A RESPONDING TO NATURAL ELICITORS SPRAYING: FOCUSING ON NATURAL PRODUCTS AND PLANT STRESS. A MINI NARRATIVE REVIEW - Ismail M. A. M. Shahhat*, (Chelonian Research Foundation, 2024)
Lamiaceae is the largest family in the order Lamiales, with 236 genera and over 7,000 flowering plant species. Known as the mint family, it is important for its aromatic leaves and medicinal properties. Stresses affect plant physiology, prompting the production of secondary metabolites. Elicitors accelerate secondary metabolite formation in plants. By the present review, Web of Science, Scopus, Google Scholar, PubMed and Science Direct databases were referred to collect information about natural elicitors (amino acids, polyamines, yeast, seaweeds and plant extracts). This present work reviewed the literature from 2015 to march 2024. The aim of this work is to highlight the recent in the impact of natural elicitors on secondary metabolite accumulation and plant stress in Lamiaceae. Foliar spraying of natural elicitors induced changes in plants, such as increased volatiles accumulation and alterations in essential oil composition, phenolic contents, and total flavonoids, as well as antioxidant enzymes. Variations in growth, oil composition, and yield were observed in different plant species in response to drought and salinity stress. The plants adapted by changing their physiological activities to produce secondary metabolites. Spraying Natural elicitors effectively reduces the damage of oxidative stress and mitigates the negative effects of salinity, water deficit, and heavy metals on secondary metabolites in plants of the Lamiaceae family, leading to plants of this family adapting to conditions of various environmental stresses. Review showed that focusing on Ocimum genus; importance of studying various biological extracts especially on plant extracts on Lamiaceae genus, including diverse species like Chia (Salvia hispanica L.). Keywords: Lamiaceae, Natural- Elicitors, Foliar spraying, Secondary Metabolites, Plant Stress.